Adjuvant treatment and survival in older women with triple negative breast cancer: A Surveillance, Epidemiology, and End Results analysis. Issue 3 (29th March 2019) - Kozak, Margaret M.; Xiang, Michael; Pollom, Erqi L.; Horst, Kathleen C.
Abstract: Patients with triple negative breast cancer were identified using the Surveillance, Epidemiology, and End Results database. Competing risks analysis was used to assess the cumulative incidence of breast cancer‐specific mortality (BCSM). Multivariable Fine‐Gray regression was used to identify predictors of BCSM. Women age 70+ (n = 4221) were less likely to receive chemotherapy and radiation treatment ( P < 0.0001) and had higher BCSM compared to younger women ( P < 0.0001). There were no differences in BCSM in patients who received adjuvant treatment ( P = 0.10). Stage II patients derived the greatest relative and absolute benefit from adjuvant treatment. Age was not a significant predictor of BCSM.